Attitude in Using Artificial Intelligence (AI) Tools Among Public School Teachers and its Teaching Effectiveness - Mariam J. Abarte; Joy B. Saldana; Gerald T. Malabarbas (American Journal of Education and Technology, 2026)
Artificial intelligence (AI) and digital technology continue to reshape learning, access to information, and instructional practices, yet their effective classroom integration depends largely on teachers’ knowledge, attitudes, and patterns of technology use. This study assessed the attitude toward and perceived effectiveness of AI tools among public school teachers in Sto. Niño District, Schools Division of Samar, for the School Year 2025–2026. The study employed a descriptive-causal comparative research design. Findings revealed that the respondents were predominantly mid-adults, female, married, holding bachelor’s degrees only, considered mid-career teachers, and primarily teaching at the elementary level. Teachers commonly used smartphones and laptops, frequently used gadgets daily, were familiar with widely accessible AI tools, and generally had access to basic ICT resources. Teachers demonstrated a positive attitude toward theoretical knowledge, indicating awareness and understanding of AI concepts, but only moderate levels of practical knowledge and pedagogical use, suggesting limited classroom application. The effectiveness of AI tools was rated positively across all dimensions, particularly in personalized training, time efficiency, research, data-driven inputs, and enhanced learning engagement. There were no significant differences in attitude levels when grouped by most demographic variables. Significant differences in perceived effectiveness were observed only when teachers were grouped by grade level. Among the technology-related variables, only the frequency of gadget use significantly predicted effectiveness, while the type of device, the AI tools commonly used, and the presence of other ICT resources did not. The findings highlight a gap between teachers’ conceptual understanding and actual classroom integration of AI. The study recommends hands-on ICT integration training to strengthen practical skills and pedagogical application, thereby improving the effectiveness of AI use in teaching.